SAT0457 Reduced Hip Cortical Porosity with Denosumab (DMAB) Treatment in Women with Osteoporosis. (10th June 2014) - Zebaze, R.M.; Libanati, C.; McClung, M.R.; Zanchetta, J.R.; Kendler, D.L.; Høiseth, A.; Wang, A.; Ghasem-Zadeh, A.; Seeman, E.
Abstract : Background: Cortical mass and structure (i.e., porosity, thickness, area) influence bone strength, and contribute to nonvertebral fracture risk. Cortical porosity, a reflection of the degree of structural decay associated with exponential worsening of bone fragility, is the result of unbalanced and accelerated intracortical remodeling causing canals to enlarge and coalesce thereby fragmenting the cortex. While reducing remodeling will limit worsening of porosity, reversing porosity should be considered for individuals already at increased risk of fracture. We previously reported that hip cortical mass and thickness improved over 3 years of DMAb administration, which could be explained by infilling of porosity in the inner cortical region adjacent to the medullary canal. Objectives: To evaluate changes in hip porosity using a subset of multi detector computed tomography (MDCT) hip images from the FREEDOM study. Methods: In FREEDOM, a 3-year, randomized, double-blind trial that enrolled postmenopausal women with osteoporosis, women received placebo (Pbo) or 60 mg DMAb every 6 months. Percentage porosity in both the compact and trabecularized (outer and inner transitional zones) cortical volumes of the subtrochanter region were measured using StrAx1.0 software (Zebaze et al., Bone 2013) from MDCT hip images obtained at baseline and year 3 (Pbo, n=22; DMAb, n=28). Results: At baseline, 72% of volume was occupied by porosity in the inner transitional zone adjacent to the medullary compartment, 37% in the outer transitional zone, and 29% in the compact-appearing cortex. Cortical porosity correlated positively with serum CTX ( p =0.017) and negatively with hip strength estimated using finite element analysis ( p =0.027). At year 3, DMAb reduced porosity compared with baseline and Pbo across the entire cortex (Figure) and all compartments; treatment effect (DMAb–Pbo) improvements were –5.3% (overall), –1.8% (inner transitional zone), –5.6% (outer transitional zone) and –7.9% (compact-appearing cortex; all p <0.001). Conclusions: Denosumab administration was associated with reversal of hip cortical porosity in postmenopausal females with osteoporosis. Since improvements in cortical porosity equate to increased mineralized bone matrix and both are relevant to strength, this structural cortical amelioration helps explain the observed significant reductions in hip fractures associated with DMAb administration. Acknowledgements: Study sponsor and abstract preparation Amgen/GSK Disclosure of Interest: R. Zebaze: None declared, C. Libanati Shareholder of: Amgen, Employee of: Amgen, M. McClung Grant/research support: Amgen, Merck, Consultant for: Amgen, Lilly, Merck, Novartis, Warner-Chilcott, J. Zanchetta Grant/research support: Amgen, MSD, Radius Inc, Consultant for: Amgen, Eli Lilly, MSD, GSK, D. Kendler Grant/research support: Amgen, Eli Lilly, Novartis, Pfizer, GSK, J&J, Consultant for: Amgen, Eli Lilly, Novartis, Pfizer, Warner Chilcott, A. Høiseth: None declared, A. Wang Shareholder of: Amgen, Employee of: Amgen, A. Ghasem-Zadeh Shareholder of: StrAx Corp-one of the inventer of StrAx 1.0 (analysis software), E. Seeman Shareholder of: Director StraxCorp, Grant/research support: Amgen, MSD, Consultant for: Amgen, Sanofi aventis, MSD, Eli Lilly, Novartis, Warner Chilcott DOI: 10.1136/annrheumdis-2014-eular.1221